Evaluation of the relationship between occupational balance and quality of life in pregnant and non-pregnant women - Didem Simsek Kucukkelepce; Nurcan Gokgoz; Filiz Polat; Azize Reda Tunc (BMC Pregnancy and Childbirth)
Abstract Background Occupational balance plays a crucial role in maintaining overall well-being and quality of life, particularly during pregnancy, a period marked by significant physiological, psychological, and social changes. This study aims to evaluate the relationship between occupational balance and quality of life in pregnant and non-pregnant women. Methods This analytical cross-sectional study was conducted in a foundation university hospital with 220 participants, 110 pregnant women in different trimesters of pregnancy (case group) and 110 non-pregnant women (control group). Participants were selected through a purposive sampling method from among volunteers who applied to the pregnancy clinic and hospital for various reasons. Data collection instruments included the Personal Information Form, the Occupational-Role Balance Questionnaire-11 Turkish Version (OBQ11-T), and the SF-12 Quality of Life Scale. Statistical analyses were performed using SPSS 20.0, employing t-tests, chi-square tests, Pearson correlation, and regression analysis to determine relationships between variables. Statistical significance was considered at p < 0.05. Results No statistically significant differences were found between the groups regarding age, education, employment, and income status. The mean OBQ11-T score was higher in the case group (28.77 ± 6.54) than in the control group (26.30 ± 6.43) (p = 0. 005). SF-12 Physical Component Summary (PCS) scores were significantly higher in the case group (53.95 ± 9.34) compared to the control group (45.44 ± 10.89) (p = 0.000), while the Mental Component Summary (MCS) scores showed no significant difference. A weak but positive correlation was identified between OBQ11-T and the PCS subdimension of SF-12 in both groups (case: r = 0.229, p = 0.016; control: r = 0.209, p = 0.028). Regression analysis revealed that OBQ11-T scores were a significant predictor of SF-12 PCS scores (β = 0.229, R = 0.229; R² = 0.052; p = 0.016). Regression analysis indicated that occupational balance accounted for 5% of the variance in PCS scores. This finding reveals that as the level of occupational balance increases, participants’ perceptions of quality of life related to physical health also increase slightly. Conclusion Women in both groups demonstrated above-average occupational balance scores, and a weak but positive relationship was observed between occupational balance and the physical component of quality of life. Therefore, it may be useful to develop strategies to protect and maintain occupational balance, especially in order to support quality of life related to physical health.